(untitled) (Nativa, 2024)
Small farmers face many challenges regarding financial inclusion, which adversely affect farm productivity and reduce their income and welfare, especially in developing countries. An optimal comprehension of financial services in specific contexts is a significant challenge, especially for smallholders. So, the question is obvious: Why do small farmers have less access to credit? The main purpose of the present study is to estimate the impact of the determinants of credit access in the Peruvian agricultural sector from 2015 to 2019, considering farm size in different geographic areas, using an econometric methodology for cross-sectional data. The study used data extracted from the Peruvian National Agricultural Survey. The results reveal the probability of farmers accessing credit. However, it varies according to farm size, and was, on average, around 30% at the national level, whereas the size of the farms was identified as a crucial factor. Being a smallholder reduces farmers’ probability of access to credit, while being a large-scale farmer nearly doubles this probability. Furthermore, the study estimated the trend in the odds ratios, which are associated with certain characteristics of the farming population in Peru. Keywords: financial inclusion; agricultural finances; credit invisibility; smallholders. Por que os pequenos agricultores têm menos acesso ao crédito? uma análise de microdados do caso Peruano RESUMO: Os pequenos agricultores enfrentam muitos desafios com relação à inclusão financeira, que têm efeitos adversos sobre a produtividade agrícola e reduzem sua renda e seu bem-estar, especialmente nos países em desenvolvimento. A compreensão ideal dos serviços financeiros em contextos específicos é um desafio significativo, especialmente para os pequenos agricultores. Portanto, a pergunta é óbvia: Por que os pequenos agricultores têm menos acesso ao crédito? O principal objetivo do presente estudo é estimar o impacto dos determinantes do acesso ao crédito no setor agrícola peruano de 2015 a 2019, considerando o tamanho das fazendas em diferentes áreas geográficas, usando uma metodologia econométrica para dados transversais. O estudo usou dados extraídos da Pesquisa Agrícola Nacional do Peru. Os resultados revelam que a probabilidade de acesso ao crédito pelos agricultores, embora varie de acordo com o tamanho da fazenda, foi em média de cerca de 30% em nível nacional, enquanto o tamanho das fazendas foi identificado como um fator crucial. O fato de ser um pequeno produtor reduz a probabilidade de acesso ao crédito, enquanto o fato de ser um grande produtor quase dobra essa probabilidade. Além disso, o estudo estimou a tendência dos índices de probabilidade, que estão associados a determinadas características da população agrícola no Peru. Palavras-chave: inclusão financeira; finanças agrícolas; invisibilidade do crédito; pequenos proprietários.